ANTI-INFLAMMATORY ACTIVITY OF MANILKARA ZAPOTA LEAF EXTRACT - Konuku, Kamalakararao; Karri, Krishna Chaithanya; Gopalakrishnan, Velliyur Kanniappan; Hagos, Zenebe; Kebede, Haftom; Naidu, Tentu Kasi; Noyola, Patricia Ponce; Palleti, John Dogulas; Rao Duddukuri, Govinda Rao Duddukuri (International Journal of Current Pharmaceutical Research, 2017)
Objective: Manilkara zapota is a medicinal plant which is native to Mexico and Central America, and widely distributed in India. Various parts of this plant are traditionally used for treatment of several diseases, including inflammation-associated ailments. The main aim of the present study is to evaluate the anti-inflammatory potential of ethyl acetate and methanolic extracts of M. zapota leaf. Methods: In vitro secretary phospholipase A2 (PLA2) and 5-Lipoxygenase (5-LOX) assays and In vivo studies using carrageenan induced rat paw edema model were performed to assess the anti-inflammatory activity of M. zapota leaf extracts. Results: In vitro studies suggest that M. zapota leaf extracts exhibited significant SPLA2 and 5-LOX inhibitory activities. In in vivo studies M. zapota leaf extracts showed dose dependent inhibition of carrageenan induced paw edema in rats. The anti-inflammatory activity of ethyl acetate leaf extract was superior to methanolic extract. Conclusion: This study concluded that ethyl acetate leaf extract of M. zapotaexhibited significant anti-inflammatory activity and warranted further investigation to isolate and identify the components. Â